2021
DOI: 10.1002/acn3.51453
|View full text |Cite
|
Sign up to set email alerts
|

Role of cellular prion protein in splenic CD4+ T cell differentiation in cerebral ischaemic/reperfusion

Abstract: Objective Cellular prion protein (PrPC), the primary form of prion diseases pathogen, has received increasing attention for its protective effect against ischaemic stroke. Little is known about its role in peripheral immune responses after cerebral ischaemia/reperfusion (I/R) injury. This study is to detect the variation of splenic CD4+ T lymphocytes differentiation and the concentration of inflammatory cytokines after murine cerebral I/R injury in the context of PRNP expression as well as its influence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While it is unclear what the primary function of the prion protein is, it has been shown that it is protective under neuronal stress conditions. PrP expression is increased in the plasma of stroke patients, and it protects neurons from apoptosis [66]. Also, there is evidence that PrP protects cells under oxidative stress conditions from senescence.…”
Section: Cd16+ Monocytes and Toll Like Receptormentioning
confidence: 99%
“…While it is unclear what the primary function of the prion protein is, it has been shown that it is protective under neuronal stress conditions. PrP expression is increased in the plasma of stroke patients, and it protects neurons from apoptosis [66]. Also, there is evidence that PrP protects cells under oxidative stress conditions from senescence.…”
Section: Cd16+ Monocytes and Toll Like Receptormentioning
confidence: 99%
“…In recent years, many robust evidences have been yielded from animal models that CD4 + T cells play an important role in ischemia-reperfusion ( 26 , 27 ). CD4 + T cells are widely involved in reperfusion injury, not limited to myocardial tissue ( 28 ). CD4 + T cells mediate hepatic neutrophil recruitment and liver injury during hepatic ischemia-reperfusion ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…This IL-13 elevation might be attributed to the enhanced proportion of T helper-2 (Th2) cells, the main source of IL-13. The Th2 response that secretes anti-inflammatory cytokines such as IL-4 and IL-13 was found to decrease after CI/RP [50], resulting in enhanced neuronal death [51,52]. Th2 cells prove to ameliorate functional disturbance after CI/RP [53], and some bioactive components of SGD, such as paeoniflorin [54] and glycyrrhizin [55], have been reported to modulate Th2 response, thereby increasing the expression of IL-13.…”
Section: Discussionmentioning
confidence: 99%